The Translator's Amanuensis 2020 - Elisa Alonso; Lucas Nunes Vieira (JoSTrans: The Journal of Specialised Translation)
This paper is an exercise of imagination. Based on Kay's (1980) inspiring idea of a translator's amanuensis, we attempt to describe a post-editing tool that enables ubiquitous translation (Cronin 2010). We argue that a parallelism exists between media remediation (Bolter and Grusin 1999) and the shifting phase translation is undergoing, with machine translation post-editing having an impact on the global workflow of translated content. We take the hybridisation of traditional and machine translation processes as a starting point to envisage the features of forthcoming translation technologies. Results of previous surveys helped us to select features expected to play a central role: versatile devices to which we broadly refer as displayers would enable ubiquity; a relevant knowledge feature would provide human translators with a well-assorted repertoire of reliable sources; and an effort prediction feature would provide post-editors with reliable estimates of how much work lay ahead. Interacting with the Translator's Amanuensis 2020 would not always be straightforward, however. Translators will have to adapt to richer ways of reading and visualising information. Ultimately, we argue that the Translator's Amanuensis 2020 could benefit from existing Translation Studies concepts: the study of translation problems, translation competence models, and the ethics and sociology of translation.